550Short-term exposure to grass pollen is associated with lower lung function and increased airway inflammation. (2nd September 2021) - Sabrina Idrose, N.; Tham, Rachel; Lodge, Caroline; Lowe, Adrian; Bui, Dinh; Perret, Jennifer; Vicendese, Don; Newbigin, Ed; Tang, Mimi; Aldakheel, Fahad; Douglass, Jo; Abramson, Michael; et al.
Abstract: Background: The association between grass pollen exposure and lung function changes and airway inflammation is limited. We investigated these associations in a community-based sample, and whether any such associations were modified by current asthma, current hay fever, pollen sensitization and age. Methods: Cross-sectional analyses of data from the Melbourne Atopy Cohort Study (MACS) participants (n = 936). Lung function was assessed using spirometry. Airway inflammation was assessed by fractional exhaled nitric oxide (FeNO), and exhaled breath condensate pH and nitrogen oxides (NOx). Daily pollen counts were collected using a volumetric spore trap. The associations were examined by linear regression. Results: Higher ambient levels of grass pollen 2 days before (lag 2) were associated with lower mid-forced expiratory flow (FEF25-75% ) and FEV1 /FVC ratio (Coef. [95% CI] = -119 [-226, -11] mL/s and -1.0 [-3.0, -0.03] %, respectively) and also 3 days before (lag 3). Increased levels of grass pollen a day before (lag 1) was associated with increased FeNO (4.35 [-0.1, 8.7] ppb) and also at lag 2. Adverse associations between pollen and multiple outcomes were greater in adults with current asthma, hay fever and pollen sensitization. Conclusions: Grass pollen exposure was associated with eosinophilic airway inflammation 1-2 days after exposure and airway obstruction 2-3 days after exposure. Key messages: There is a more delayed effect on lung function compared to airway inflammation. Adults with current asthma, hay fever and grass pollen sensitisation are especially vulnerable.